Management of Acute Wilsonian Hepatitis with Severe Hemolysis: A Successful Combination of Chelation and MARS Dialysis. (11th May 2021) - Hassoun, Jeremy; Hammer, Nathalie; Magini, Giulia; Ponte, Belen; Ongaro, Marie; Rougemont, Anne-Laure; Goossens, Nicolas; Frossard, Jean-Louis; Spahr, Laurent
Abstract : Wilson's disease is a rare hereditary disorder of copper metabolism leading to progressive accumulation of copper in several organs including the brain and the liver. Acute liver failure is a relatively rare hepatic manifestation of WD which may require urgent liver transplantation if medical treatment fails. We report here the case of a young woman who presented with classic acute Wilsonian hepatitis complicated by liver and renal failure and a severe hemolysis related to massive nonceruloplasmin bound copper accumulation requiring repeated blood transfusions. The early initiation of a combined treatment including conventional chelation therapy and repeated MARS dialysis sessions allowed a rapid control of hemolysis, a progressive decrease of free copper overload, and clinical recompensation without liver transplantation.